’आयाम’ कथामा सांस्कृतिक चेतना - Ghodasaini, Khagendra (Haimaprabha, 2025)
This article has been prepared by reviewing the story ‘Ayam’ from the perspective of cultural consciousness. In this article, conclusions have been drawn by studying the facts obtained in the work based on cultural consciousness. In it, the problem of widowed women is described and the idea of ​​cultural change is given a place. This article is structured in a qualitative format, purposeful sample selection methods and facts have been collected from the work. In this, marriage rituals have been made a theoretical concept. Basically, literature focuses on various aspects of society and culture. In this story, social and cultural problems have been raised and their solutions have been given. Therefore, cultural consciousness related to marriage has been made the basis of analysis in this text. When analyzing the cultural consciousness of Yangji, Shantamaya, Ama, Suraj and Sanu Tamang under cultural consciousness in the story ‘Ayam’, their consciousness is seen to be different from the tradition. They understand the problems of widows and widowers and understand the human feeling. It is shown that the natural culture that suppresses people should be changed. At a time when widow remarriage has not become an acceptable issue in Nepali society, Suraj, like Yangji, Ama and Shantamaya, also seems to be in favor of it. Since consciousness is perfected through behavior, the transformative behavior seen in the characters of the story Ayam is the result of cultural consciousness. From this, it has been concluded that the story ’Ayam’ uses a consciousness different from traditional social and cultural norms by depicting the different problems, experiences and hardships of widowhood of widowed women in the age groups of 25, 30 and 49.